Dilema hukum dalam penetapan harga tandan buah segar sawit: Analisis terhadap peran negara dalam menjamin keseimbangan pasar - baiti, nur; Hasan, Akhmad Farroh (Maliki Interdisciplinary Journal, 2025)
The pricing of Fresh Fruit Bunches (FFB) of oil palm in Indonesia is a central issue that has a direct impact on the welfare of farmers and the sustainability of the national palm oil industry. Although regulations such as the Regulation of the Minister of Agriculture No. 13 of 2024 have been issued, which replaces the Regulation of the Minister of Agriculture No. 1 of 2018, implementation in the field is still marked by price disparities between partner and non-partner farmers, company dominance in pricing, and the weak bargaining position of independent farmers. The regulation of FFB prices normatively provides protection and transparency, but is still weak in terms of law enforcement due to the absence of strict sanctions for violators of the reference price. The state is faced with a dilemma between protecting small farmers and maintaining an investment climate, so that fair and proportional public policies are needed. This article analyzes the effectiveness of FFB price regulations, the role of the state in ensuring market balance, and offers solutions in the form of strengthening institutions, establishing independent price monitoring institutions, digitizing price information, and strengthening farmer cooperatives. The results of the study emphasize the need for synergy between stakeholders and strict enforcement of sanctions so that justice and the welfare of oil palm farmers can be realized sustainably.